The Effect Of Understanding Regional Financial Accounting Systems, Regional Financial Management And Accountability On Opd Performance With Supervision As Moderating Variables In - Morita Rahel Promovenda, Bella; Br Bukit, Rina; Gaddafi, Muammar (Riviera Publishing, 2022)
The changes that have taken place since the beginning of the 1998 reform have brought changes to national development, including the performance of the regional organization (OPD) with supervision as a moderating variable in the provincial Government of North Sumatra. Population of this research is the Budget User Authority, the Technical Activities Executive Officer, Financial administration officer across the regional working units. The sampling technique used is the saturated sampling technique. The number of OPD is The hypotheses were analyzed using the Structural Equation Model (SEM) method with the help of SmartPLS 3.0 software. The results of this study were the understanding of the regional financial accounting systems,regional property management, accountability influence the Regional Working Unit Performance simultaneously. Supervision has no positive effect and does not significantly moderate the influence of Regional Financial Management on Performance OPD the Provincial Government of North Sumatra